Analisis Biaya Layanan yang Tinggi Dalam Transaksi Pinjaman Online Pada Bisnis Fintech Adakami - Nugraha, Michael Adi; Ardiansyah, Aan Ilham; Panggabean, Jefry Stephen (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Online loans are facilities for borrowing money by certain bodies by utilizing online technology. Pinjol has grown rapidly in Indonesia in the last three years because the administration requirements are easier compared to banking financial service loans. Fintech itself is a type of company that innovates by utilizing modern technology so that it can provide new added value in the field of financial services. One of the fintech companies, AdaKami, is a peer to peer lending platform managed by PT. Indonesian Digital Financing which provides online credit without collateral and also installment payments with transparent fees.